High Frequency of Cell-in-Cell Formation in Heterogeneous Human Breast Cancer Tissue in a Patient With Poor Prognosis: A Case Report and Literature Review - Ruan, Banzhan; Niu, Zubiao; Jiang, Xiaoyi; Li, Zhuo; Tai, Yanhong; Huang, Hongyan; Sun, Qiang (Frontiers in Oncology, 2019)
Cell cannibalism is a unique pathological phenomenon that has been observed at low frequency in a variety of human tumor samples (<0.5%), including breast cancer. Cannibalistic cells typically form cell-in-cell (CIC) structures characterized by enclosure of one cell or more by another, mediating a novel type of cell death “entosis,” which was proposed as the type IV cell death. A large number of CIC structures are generally associated with malignant transformation and progression, and they are believed to be primed by and form among heterogeneous cells. However, there is currently no in vivo evidence from human tumor samples. In this case report, covering a 37-year-old female breast cancer patient, we observed considerable heterogeneity and proliferative activity (>70% Ki-67 positivity) in her breast cancer cells, accompanied by high frequency of CIC formation ( 6%) and poor prognosis. We consider this a typical example of cell cannibalism, supporting a role of heterogeneity in cell-in-cell formation and malignant progression. It may serve as a pretest basis for further investigations of cell-in-cell biology and breast cancer treatment.